Impact of Organizational Culture and Discipline on Employee Performance: A Study of Cooperative Members - Irman Firmansyah; Raden Rijanto; Tedi Pitri (Jurnal Bisnis, Manajemen, dan Ekonomi, 2023)
The smooth running of cooperative activities amid massive changes is inseparable from aspects of organizational culture, enforcement of discipline and employee performance that is in line with shared expectations and goals. Organizational culture as a philosophy that is embraced together can be used as a direction to excel and advance together, the high discipline of the members is believed to be able to make the best contribution to the development of the cooperative through its maximum performance in an effort to create mutual benefits. This study aims to find out and re-analyze the relationship between organizational culture and discipline in predicting and influencing employee performance in cooperatives. The sample of this study was 34 respondents selected using the total sampling technique. Research findings, organizational culture and discipline have a positive effect on employee performance both individually and simultaneously. The contribution of the influence of organizational culture on employee performance is more dominant than the influence of discipline. It is important for cooperative management to evaluate employee performance regularly and scheduled so that improvements can be made gradually and continuously, strengthening understanding of organizational culture and disciplinary action as part of the evaluation. Organizational culture is more dominant than discipline in influencing employee performance, the causal factors in detail are not explained, and this can be a consideration for subsequent research. Digital aspects relevant to cooperative activities and management systems can also be considered to conduct investigations on employee performance in the era of technological disruption, in Industry 4.0.